Mengembangkan Kecerdasan Emosional Anak - Retno Tri Hariastuti, ; Abdul Saman, (Pendidikan Dasar, 2007)
As a future generation, a child should be given education and skills as early as possible, one kind of which is emotional intelligence comprising 1) moral emotion, 2) emotion of thinking skill, 3) problem solving, 4) social skill, 5) self motivation and skill to get achievement and 6) emotion strength. The method used is playing games, because through games children learn how to think, feel, take action and share with others.